GOLD SAVINGS AT PAWNSHOPS IN THE PERSPECTIVE OF ISLAMIC LAW - Nanda Kurnia Putra; Idad Difaul Haq; Rizka Rizka; Muthoifin (Universitas Muhammadiyah Surakarta, 2024)
Saving assets in the form of gold is a form of safeguarding the value of the property from inflation. Pawnshops has service products in the form of gold savings in the form of gold balance deposit services that make it easier for people to invest in gold. Pawnshops's gold savings product allows customers to invest in gold easily, cheaply, safely, and reliably. Gold transactions use an ijarah contract with buyback, add balance (top up), transfer, and print facilities. The purpose of the research conducted by the authors in this journal is to find out how the scholars view Pawnshops Gold Savings. The research method used is normative juridical which is a literature study based on law and is carried out by examining library materials or secondary data. Based on the discussion in this study, it can be concluded that Pawnshops makes gold savings products with buying and selling (Murabaha) and leasing (ijarah) services. Trading or investing in non-cash gold at a pawn shop is legally permissible as long as gold is not used as the official medium of exchange (money). However, there are some limitations and conditions that must be met